Insights Into Coronary Artery Lesions in Kawasaki Disease - Zhang, Danfeng; Liu, Lingjuan; Huang, Xupei; Tian, Jie (Frontiers in Pediatrics, 2020)
This review summarizes recent advances in understanding the development of coronary arteritis in Kawasaki disease. Kawasaki disease is the most common cause of acquired heart disease among children characterized with coronary artery abnormalities, which can cause myocardial ischemia, infarction, and even death. The pathogenic factors of Kawasaki disease and the pathological process of coronary artery disease are not clear at present, which brings challenges to the prevention and treatment of the disease. The treatment of Kawasaki disease focuses mainly on timely administration of intravenous high doses of immunoglobulin and aspirin. However, there are still some patients who do not respond well to this standard treatment, and its management remains a challenge. As a result, coronary artery lesions still occur in patients and affect their quality of life. In this review, we discuss updated research data of Kawasaki disease coronary artery lesions.